EMERGING SUPPORT MEASUREMENT BASED E-LEARNING TO HIGHER EDUCATION SYSTEM - Senthilkumar, M; Prabakaran, M (International Journal of Computer Sciences and Engineering, 2025)
In this work developing e-learning are adopting the replica approaches used by online higher education user. Elearning can provide the numerous benefits to the institutions such as accessing education at any time connecting to each other’s. Also it’s provide enhances interactivity, integrity scalability improved by the student's academic performance in cloud service. However, sound studies and show majority of these benefits are enjoyed on institutions in the e-learning. The fundamental new idea to keep service data into mind is that the strength of online educational platform comes not just from replicating things that should be possible work in other ways, however when it is used to do things that weren't possible without it. In this propose on Emerging support measurement in Higher Education (ESMHE) this technique using user short on cloud data security initiatives. To implement the online higher educator to arrange document protected close time level less in quick information telling on the e-learning system. In this e-learning to be consider entire process of academic education such as design, knowledge on developing and creating by the wonderful employing e-learning arrangement in cloud. They are significant, and they include improved efficiency, effectiveness, and enjoyment of the learning experience system colossal idea measurement online higher education user